Respons Pertumbuhan dan Serapan Hara Fosfat Bibit Kelapa Sawit (Elaeis guineensis Jacq.) Pada Media Gambut Yang Diaplikasi Amelioran dan Pupuk Hayati - Nanda Rizky Utami; Abdul Rauf; Mariani Sembiring (Pusat Penelitian Kelapa Sawit, 2026)
This research aims to examine the effect of the application of ameliorants and biofertilizers on growth, phosphorus nutrients in the soil, and nutrient absorption in plants. This research was conducted in a greenhouse at the Faculty of Agriculture, University of North Sumatra, using peat soil, volcanic ash, zeolite, mycorrhiza, and phosphate-solubilizing bacteria. This study used a Randomized Block Design (RBD) with two factors. The first factor is biofertilizer: control, phosphate-solubilizing bacteria (PSB), arbuscular mycorrhizal fungi (AMF), and a combination of PSB with AMF. The second factor is ameliorant: control, volcanic ash, zeolite, and a combination of volcanic ash with zeolite: with 3 replications. The results showed that there was an increase in the height of oil palm seedlings where the best treatment was the application of AMF (1.97% - 7.88%) and the best treatment for the application of volcanic ash (4.27% - 7.07%). In the observation of soil pH, the application of ameliorants had a significant effect (3.53% - 4.5%) on all materials, while the application of biofertilizers also had a significant effect on the increase in soil pH (1.41% - 3.84%) on all materials provided. In the observation of available phosphorus in the soil, the application of biofertilizers affected the increase in the value of available phosphorus in the soil, where the best value was from the application of PSB (10.31%), while the application of ameliorants also had a significant effect where the best treatment was the application of volcanic ash (30.63%). In the measurement of phosphorus nutrient absorption, the application of biofertilizers had a good effect (increased) (13.41%) compared to the control, but in the application of ameliorants, there was a decrease in phosphorus absorption results compared to the control with the lowest value in the application of zeolite (-1.56%). The results of this study indicate that ameliorants and biofertilizers can be recommended for marginal soils, especially peat soils, as supporting materials for the media in oil palm seedling cultivation.